Effects of electrical current and temperature on contamination-induced degradation in ohmic switch contacts. (May 2015) - Brand, Vitali; Saleh, Mohamed E.; de Boer, Maarten P.
Abstract: As scaling of silicon-based metal oxide semiconductor field effect transistor approaches its limits, the ohmic switch has recently been regarded as a viable alternative or complementary technology. However, the electrical contacts in these devices are prone to contamination from ambient hydrocarbons that reduces signal transmission through the switch. In this work we report how two key parameters, electrical current and temperature, affect contaminant-induced degradation mechanisms. It is shown that passing electrical current through the contacts significantly increases contamination growth but also increases its conductivity. We also demonstrate that increasing the ambient temperature delays and reduces the rate of contamination growth. Highlights: Adsorbed hydrocarbons transform into an insulating amorphous carbon upon mechanical cycling. Increasing temperature reduces the growth rate of the amorphous carbon deposit. Passing electrical current through the deposit makes it electrically conductive. Electrical current, not temperature, increases the deposit growth rate.